Sosialisasi Pengenalan Telemdicine Pada Masyarakat Di Wilayah Kerja Puskesmas Lopok - Herni Hasifah; Nur Arifatus Sholihah; Iga Maliga; Ana Lestari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The Covid-19 pandemic has led to various policies whose purpose is to limit activities and suppress the rate of spread. These restrictions make it difficult for people to seek medical treatment for those who are exposed. The government then introduced telemedicine as an online/virtual medical service that allows medical personnel to provide health services. However, the use of telemedicine is not fully understood by most Indonesians. The purpose of this activity is to increase the understanding and knowledge of the community and foster a sense of trust in the community so that they are willing and able to use telemedicine services as a preventive measure in dealing with certain health conditions. Activities are carried out using the door to door method and involve students as technical implementation assistants. Based on the results of the activity, it is known that before this service activity, the community did not know and did not recognize telemedicine. However, after this activity took place, the community was interested in using the telemedicine application and better understood the benefits of telemedicine.